PENGARUH RETURN ON EQUITY, EARNING PER SHARE DAN DEBT TO EQUITY RATIO TERHADAP RETURN SAHAM PADA SEKTOR TEKSTIL DAN GARMEN TAHUN 2020-2023 - Febrian, Faisal; Artati, Dwi (LP2M Universitas Perjuangan Tasikmalaya, 2025)
This study aims to explore the impact of return on equity, earnings per share, and debt to equity ratio on stock returns in the textile and garment sector listed on the Indonesia Stock Exchange during 2020 to 2023. The population analyzed in this study includes 23 companies listed on the IDX during that period. The sampling method used is purposive sampling, which resulted in 9 companies as samples, with data taken for 4 periods resulting in a total of 36 data. To analyze the data, we used multiple linear regression with the help of SPSS 27 software. The findings of this study indicate. That return on equity and earnings per share have an impact on stock returns, while debt to equity ratio does not show any effect on stock returns.